2016
DOI: 10.1007/s12283-016-0197-7
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional forward dynamic model of the golf swing optimized for ball carry distance

Abstract: A 3D predictive golfer model can be a valuable tool for investigating the golf swing and designing new clubs. A forward dynamic model, which includes a four degree of freedom golfer model, a flexible shaft based on Rayleigh beam theory, an impulse-momentum impact model and a spin rate dependent aerodynamic ball model, is presented. The input torques for the golfer model are provided by parameterized joint torque generators that have been designed to mimic muscle torque production. These joint torques are optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…In recent studies by Mackenzie and Sprigings [2] and Balzerson et al [3], a four DoF golfer model incorporating a flexible club was shown to provide close comparison to experimental kinematics and kinetics of a low-handicap golfer. This model is represented in Figure 1.…”
Section: Golfer Modelmentioning
confidence: 84%
See 2 more Smart Citations
“…In recent studies by Mackenzie and Sprigings [2] and Balzerson et al [3], a four DoF golfer model incorporating a flexible club was shown to provide close comparison to experimental kinematics and kinetics of a low-handicap golfer. This model is represented in Figure 1.…”
Section: Golfer Modelmentioning
confidence: 84%
“…Revolute joints between bodies represent the torso, shoulder, forearm, and wrist joints. As with the model used in [2,3], the torso was inclined 30掳 to the vertical, and the swing plane of the arms was rotated 50掳 from the horizontal. Body segment inertial parameters matching another advanced biomechanics golfer model were used in this study, including location of the hips above the ground [4].…”
Section: Golfer Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The torque values were scaled at each time point based on the joint angle and angular velocity to represent the muscle force-velocity and force-length relationships. Each joint had a maximum rate of torque development that was based on muscle activation and deactivation time constants used by Balzerson et al [4]. Passive joint torques were also included for each joint.…”
Section: Cyclist Modelmentioning
confidence: 99%
“…This reduces the number of variables and simplifies the optimal control problem. Joint torque models have been implemented extensively in predictive simulation of human movement, especially with sports applications [3,4].…”
Section: Introductionmentioning
confidence: 99%